Upaya Meningkatkan Kesadaran Membaca di Perpustakaan pada Siswa Kelas 7 SMP Darussalam Cimanggu - Helmi Seftiani; Sigit Andi Prasetya Dinata; Arista Etania Putri (Universitas Muhammadiyah Manado, 2022)
Reading awareness is one of the main foundations in the world of education that supports the development of students' insights, critical thinking skills, and academic success. However, the low awareness of reading among 7th grade students of SMP Darussalam Cimanggu is a challenge that needs to be overcome immediately. This study aims to identify the factors that affect low reading awareness and design effective strategies to improve it. The research method used is a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation studies. The results of the study show that the lack of internal motivation, lack of family support, the influence of technology, and the low attractiveness of library facilities are the main causes of low reading awareness of students.